Ghana: The limits of external democracy assistance - E. Gyimah-Boadi; Theo Yakah (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Ghana's experience since the early 1990s indicates that external aid can significantly impact a country';s democratic transition. External democracy assistance has been a crucial, positive factor in Ghana's steady evolution into an electoral democracy over the past two decades. Continuing gaps in the quality of Ghana's democracy confirms, however, that even sustained external support and encouragement cannot easily overcome local elite resistance to specific reforms as well as structural and cultural obstacles prevailing in the domestic environment, at least in the short and medium terms.
Keywords: D72; F35; N47; 330; Ghana; electoral democracy; foreign aid; Entwicklungshilfe; Demokratisierung; Ghana